An introduction to property marketing first edition - Mar Iman, Abdul Hamid (Fakulti Kejuruteraan Dan Sains Geoinformasi, 2007)
This book contains several chapters like table of contents part I, property marketing environment, introduction to property marketing, the concept of marketing what marketing is not the goals of real estate marketing, basic problems in relation to real estate marketing, functions of marketing, role and functions of marketing department, characteristics of real estate in relation to marketing, marketing management, introduction, principles of marketing management, marketing management philosophies, roles and functions of a marketing manager, marketing management process, project and sales cycle, understanding the property market, the characteristics of property market, general factors affecting property supply and demand, some aspect Malaysian property market, implications of the property market on property marketing, property marketing planning, the concept of strategic planning, reactive versus proactive planning, short term versus long term planning, three main aspects of strategy, organisational structure, the organisational approach to marketing, corporate resources, the preparation of marketing plan, internal and external environment in property marketing, the internal environment: working as a team, the external environment: facing the challenge, consumer behaviour, introduction, factor influencing consumers, behavioural model of real estate, emulsion of the influences in marketing.